External morphology and oral cavity of the tadpole of Trachycephalus atlas Bokermann, 1966 (Amphibia, Anura, Hylidae) - Barreto, Gilvana Santos; Ramos, Juliana Conceição; Mercês, Ednei De Almeida; Napoli, Marcelo Felgueiras; Garda, Adrian Antonio; Juncá, Flora Acuña (Zootaxa, 2015)
The Neotropical genus Trachycephalus Tschudi currently comprises 14 species distributed in lowlands of Mexico, Central and South America east of the Andes, south until northern Argentina (Frost 2014) and throughout Brazil (IUCN 2014). Seven species of the genus have tadpoles formerly described: T. coriaceus (Peters) (Schiesari & Moreira 1996; Lescure et al. 1996), T. cunauaru Gordo, Toledo, Suárez, Kawashita-Ribeiro, Ávila, Morais & Nunes (Grillitsch 1992 as Phrynohyas resinifictrix according to Gordo et al. 2013), T. jordani (Stejneger & Test) (McDiarmid & Altig 1989-1990), T. mesophaeus (Hensel) (Lutz 1973; Carvalho-e-Silva et al. 2002; Prado et al. 2003), T. nigromaculatus Tschudi (Wogel et al. 2000), T. resinifictrix (Goeldi) (Hero 1990; Schiesari et al. 1996), and T. typhonius (Linnaeus) (Pyburn 1967; Duellman 1970; Schiesari et al. 1996). The oral cavity is described only for T. cunauaru (Grillitsch 1992), T. resinifictrix (Schiesari et al. 1996), and T. typhonius (Schiesari et al. 1996; Fabrezi & Vera 1997).